The Role of School Libraries in Fostering Reading Culture among Junior High School Students: A Systematic Literature Review - Mufida Aly; Asya Najihatul Mutamaroh; Fitri Mutia (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2026)
Background: Students' reading skills still face serious challenges, as shown by the results of the Program for International Student Assessment (PISA). The low reading culture among students is influenced by the lack of interesting collections, suboptimal library facilities and services, the dominance of entertainment technology, and the lack of literacy activities in schools. In this context, school libraries play a role in shaping a reading culture, especially at the junior high school level.Objective: This study aims to collect and analyze findings from various research articles on the role of school libraries in promoting a reading culture among junior high school students.Methods: This study uses a qualitative approach with a systematic literature review method, which involves analyzing national and international articles from 2015 to 2025 and analyzing them using a thematic analysis method.Results: This study found that good library management, with a diverse collection and structured and systematic literacy programs, can increase students' motivation to read. The main obstacles found include inadequate library facilities, a lack of available collections, limited budgets, and low librarian competence.Conclusion: School libraries play a crucial role in building a reading culture among junior high school students. Libraries that are well managed by professional librarians and equipped with diverse collections can increase students' reading habits and motivation. A reading culture needs to be supported by structured literacy programs and collaboration between librarians and teachers.